Numerical Investigation of the Viscous Incompressible Flow Around Two Circular Cylinders in Tandem Arrangement - Phan, Duc Huynh (Old Journal, 2018)
The shedding of vortices and flow interference between two circular cylinders in tandem arrangements are investigated numerically in this paper. The two values 1.5 and 4.0 of the ratio between the distance of two cylinders and the diameter of the cylinder were used. The immersed boundary method (IBM) is used for the simulations of the two-dimensional cases. The calculations are carried out on a Eulerian-Lagrangian grid using the finite difference method. The simulations are performed using two Reynolds numbers 100 and 200. The streamline and vorticity contours of the flow around the cylinders and force time histories are presented. The calculations are also compared to results obtained by other researchers. Numerical results show that the immersed boundary method can easily solve the viscous incompressible flow past single and two cylinders in a tandem arrangement.